The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1016/j.midw.2019.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Labour characteristics of women achieving successful vaginal birth after caesarean section in three European countries

Abstract: Objective: Knowledge about labour characteristics of women achieving successful vaginal birth after caesarean section (VBAC) might be used to improve labour and birth management. This study examined sociodemographic and labour process-related factors regarding a) differences between countries, b) the comparison of successful VBAC with unplanned caesarean section, and c) predictors for the success of planned VBAC in three European countries. Design: We analysed observational data collected within the OptiBIRTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…In keeping with previous studies ( 19 , 20 ), our data showed that a previous vaginal birth is a strong predictor of the success of VBAC. Information about previous vaginal births must be included in any consultation of a patient asking for VBAC.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with previous studies ( 19 , 20 ), our data showed that a previous vaginal birth is a strong predictor of the success of VBAC. Information about previous vaginal births must be included in any consultation of a patient asking for VBAC.…”
Section: Discussionsupporting
confidence: 92%
“…The odds ratio for women with PROM to have a failed TOLAC was 4.47 (Table 5). There are limited studies into the impact of PROM on successful TOLAC, two previous studies found PROM was associated with positive outcomes [33,34]. This study found PROM was associated with increased risk of failed TOLAC (OR: 4.47, p < 0.01).…”
Section: Discussionmentioning
confidence: 67%
“…As 75% of all women entering labour and planning a VBAC in this study, had a successful VBAC, the avoidance of elective CS is key in increasing VBAC rates [34]. In terms of safety, there were two full uterine ruptures .…”
Section: Discussionmentioning
confidence: 81%